Refugees in the Horn of Africa: Political Factors Contributing to the Generation of Refugees in the Horn of Africa - Woodward, Peter (Refuge: Canada’s Journal on Refugees, 1987)
The exposure by the mass media of the conditions of refugees in eastern Sudan and of camps of displaced people in northern Ethiopia in October 1984 first alerted the world at large to the extent of the famine in that area. But clearly the problem is more complex than most people then realized, for in the Horn, refugees, famine and politics an inextricably linked.